2021
DOI: 10.4111/icu.20200438
|View full text |Cite
|
Sign up to set email alerts
|

A high basal metabolic rate is an independent predictor of stone recurrence in obese patients

Abstract: Purpose Basal metabolic rate (BMR) is an indicator of overall body metabolism and may portend unique aberrations in urine physico-chemistry and stone recurrence. The present study examined the effect of predicted BMR on 24 hours urinary metabolic profiles and stone recurrence in obese stone patients. Materials and Methods Data from 308 obese patients (body mass index [BMI] ≥30 kg/m 2 ) diagnosed with urinary stone disease between 2003 and 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The incidence of COM is higher than that of COD, and due to its hardness, fragmentation by SWL is complex compared to the other types of stones [ 21 ]. The recurrence of CaOx is dependent on several metabolic factors, including hypercalciuria, hyperoxaluria, and hyperuricosuria [ 22 ]. A 24-h urine sample should be collected to diagnose recurrent CaOx stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of COM is higher than that of COD, and due to its hardness, fragmentation by SWL is complex compared to the other types of stones [ 21 ]. The recurrence of CaOx is dependent on several metabolic factors, including hypercalciuria, hyperoxaluria, and hyperuricosuria [ 22 ]. A 24-h urine sample should be collected to diagnose recurrent CaOx stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Using RMR as a potential biomarker of body metabolic health has been supported by several previous studies. However, the conclusion drawn on the dangerous indicator of higher RMR for diseases or death appeared to predominate over its protective side (Drabsch et al., 2018; Hand & Blair, 2014; Jumpertz et al., 2011; Kang et al., 2021; Kliemann et al., 2020; Ruggiero et al., 2008; Schrack et al., 2014). An over 40‐year follow‐up of 1227 healthy participants conducted in the Baltimore Longitudinal Study of Aging (BLSA), mostly men, indicating those with high basal energy rate was associated with shorter longevity.…”
Section: Discussionmentioning
confidence: 99%
“…(Ruggiero et al., 2008) That was supported by an over 2‐year calorie restriction trial on 53 nonobese adults showing that decreased energy expenditure improved the rate of living. (Redman et al., 2018) Higher incidences of urolithiasis recurrence and diabetes were observed in the individuals with higher RMR (Kang et al., 2021). Nonetheless, diabetes and metabolic syndrome were also found more likely to occur in the population with low RMR (Buscemi et al., 2007; Georgopoulos et al., 2009; Maciak et al., 2020; Olive et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bariatric surgery is frequently associated with hyperoxaluria and stone formation, and the commonly used low-carbohydrate diets increase the risk for formation of both calcium and uric acid stones [ 11 ]. Another problem in clinical practice is that there are numerous cases in which urolithiasis develops independent of obesity [ 13 ]. Therefore, we hypothesized that not only dietary excess but also poor nutritional status may induce aberrations in urinary physicochemistry and stone recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of recurrence is as high as 30% to 50% within 10 years of the first episode; therefore, appropriate education and preventive measures are considered to be as important as the initial intervention [ 4 5 ]. A number of investigators have suggested that features of the metabolic syndrome, such as obesity, hypertension, dyslipidemia, and diabetes, which share the common underlying pathology of visceral fat accumulation and insulin resistance, are associated with urolithiasis [ 6 7 8 9 ], and numerous studies have shown high prevalences of urolithiasis and its recurrence in people with obesity [ 10 11 12 13 ]. However, despite this strong association between urolithiasis and obesity, urolithiasis develops independently of obesity in numerous patients.…”
Section: Introductionmentioning
confidence: 99%